The Non-Pharmacological Management of Shivering Post-Spinal Anesthesia - rade, agrawijaya; Sudadi, Sudadi; Yudo Pratomo, Bhirowo (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2023)
Shivering is a side effect of hypothermia which includes involuntary movements and contractions of one or more muscle groups that the patient cannot control. Perioperative shivering is a common problem during surgery under spinal anesthesia. Spinal anesthesia can cause shivering in patients because it causes distribution of internal body heat from the core of the body to the environment. Active non-pharmacological treatments for shivering post spinal anesthesia include the use of IV fluid warmed, forced-air warming, and Lower and Upper Body Forced Air Blankets. Key words: shivering, spinal anesthesia, warming of infusion fluids, forced air warming, and forced air blankets of the lower and upper body.